Da saúde à qualidade de vida - por um humanismo bakhtiniano - Oliveira, Fabrício César de (2015)
The word "Health" changed your senses throughout the XX century and their sense of contours are linked to the concept of "Quality of Life". One of the causes was the humanities approach of Medical Sciences and there is thus a kind of biopolitical power locking dialogue between areas, indicating a spectrum tends to be humanizing to distinct areas of knowledge. Health is not only biological, but biopsychosocial-ideological-discursive. Believing that there is in the origin of the term, an early unravel the clues and the humanist phantasmagoria, that would call for an analysis of the rationality of the crisis, by his closest shafts: texts and speeches. Here it is worth, in this thesis, think how Bakhtin (1895 -1975) could contribute to the Medical Sciences, even if it was even written about them. A careful analysis of the discourses of humanization and texts circulated by the official media - especially in the Folha de S. Paulo, March 2013 to November 2014 - on the program "More Doctors" (in portuguese: “Mais Médicos”) and the speech – in October 2013 - the President of the Republic, Dilma Rousseff sanctioning the law that enacted the debated health program, and are starting point for understanding the events and indications occurred and occurring changes in language, ideologies, in subjects and society. It is proposed, therefore, to discuss how heterogeneous, divergent and convergent discourses of Humanization intertwined and are constitutive of each other in the social game in building a more human science, humanistic Bakhtin called. The doctoral research was divided into an interpretation of three designs and two times: the man; the chronotope (time / space); and the Culture; looking for, at first, to understand the dialogic games and tensions that occur within the change within the word "Health". Primarily through the use of the word as ideological sign. In a second stage, took advantage of the theoretical and methodological principles of mutual comparison in GERALDI (2010 and 2012) in four stages: 1) To understand the material dimensions of the sign - the word as an ideological sign; 2) To check your social recognition; 3) To understand their context; and, 4) To interpret the active-dialogical understanding the texts on the program "More Doctors", attempting to analyze the official discourse and everyday counter-discourses tensioning changing the paradigm word "Health", at the beginning of XXI century. In short, in a world that has a tension between the mechanism and humanism, this thesis advocates the humane medicine front of purely objective and abstract technicist medicine, that is, advocates medicine as necessary reflection of the humanities.